Efecto de la suplementación de vitamina C y hierro polimaltosado sobre la hemoglobina in Rattus norvegicus: Effect of vitamin C and polymaltose iron supplementation on hemoglobin in Rattus norvegicus - Quiroz-Alvarado, Lucero Lisbet (2023)
Objetive: To determine the effect of vitamin C and polymaltose iron supplementation on hemoglobin in Rattus norvegicus. Methods: Experimental study, which consisted of dietary supplementation to 20 male Holtzman rats, randomly distributed into 4 groups. Group 0 (Control) received, like the other groups, 30 grams of daily balanced food and water ad libitum, Group 1 (Experimental 1) were administered with vitamin C (200mg/kg), Group 2 (Experimental 2) received supplementation of polymaltosate with iron hydroxide (III) 10mg/kg, and Group 3 (Experimental 3) which was administered with both study factors. In the 30 days of supplementation, each rat was provided with an individual previously acclimatized environment. During this time, two blood samples were taken for hematocrit analysis. At the end of the experiment, the 20 rats were donated to the UNT Medicine Laboratory. Results: An increase in hemoglobin levels was found in the experimental groups, Group 3 being the most significant. The collected data were analyzed by mean difference in relation to Dunnet's critical value, and the Student's T test allowed to know the relationship sample. Conclusion: Hemoglobin levels rise due to an increase in the absorption capacity of non-hemitic iron through vitamin C and the nutritional level through polymaltosate.